Knowledge Management (KM) Framework for Representing Lessons Learned System for Communities of Practice in Institutions of Higher Learning - Ahmad Sharif, Mohd Nazir; Mohamad, Kamaruddin Malik; Alias, Rose Alinda; Shahibudin, Shamsu; Zakaria, Nor Hidayati (Malaysian Journal of Computer Science, 2004)
Organisations worldwide are using techniques and technologies to better manage their knowledge. Their objective is to improve the quality of knowledge sharing by exploiting tacit and explicit knowledge of successes and failures. The requirement to record, reference and access lessons learned to support teaching operations and exercises is mainly important to lecturers in Institutes of Higher Learning. Lessons learned are typically short descriptions of specific experiences that may have future applicability in similar situations. In general, this paper proposes a KM adapted model for representing Lessons Learned System (LLS) Framework. The model was derived by mapping the Nonaka’s KM model [1] with the Lessons Learned processes that are adapted from Weber [2]. Finally, based on this model, the main features of LLS were defined and a prototype of LLS was developed. The prototype of LLS is used to illustrate the features of LLS and to demonstrate how it can be used to access Lessons Learned in order to support Communities of Practices (CoP) in Institutions of Higher Learning. LLS is a web-based application developed using WAMP which is an open source software suite comprising of Apache server, MySQL database and PHP programming for Windows operating system.